A teoria do valor em O Capital de Marx: análise das relações sociais no modo de produção capitalista - Derengoski, Gilmar (2018)
The present dissertation pretens conceptualize the value theory in Karl Marx through his most expressive book: The Capital - Critique of Political Economy - Book I - The Process of Capital Production (2013). As well as analyzing the social relationship inserted in the capitalist system mode of production. For this work, we searching demonstrate in detail the operation of capitalist system. We showing for Marx the capitalist mode of production is guid by the production and exchange of products. For this purpose we show in detail on the relationship between producers and consumers as a fundamental base for the totally operation of the system. Starting from the most simplest relationship and arriving in the most complex. For this idea we conceptualize the goods according of inseparable two sides: value of use and value of change. Then we go in to the concrete and objective relationship of the system, in the market effectively. We also going present the genesis of money-form and how this becomes universal equivalent for market changes. Evidencig the fetishistic character of the goods when the capitalist system is consolidated. Finally, we go evidencing how the accumulation of money replaces the production of goods for the human subsistence by the production of products with the objective of accumulation of money, the accumulation of riches. What finishing up conditioning reality and making appearance overcome the essence, thus transforming social relationship, which leave to be direct and concrete and become indirect and abstract.